(untitled) (Canadian Dermatology Today, 2021)
Hand eczema (HE) was already a common skin disease even pre-COVID-19, with a prevalence of about 10% in the general population. It has an important socioeconomic impact due to its high indirect health care costs and association with prolonged sick leave. Hand eczema is a clinically heterogeneous entity whose classification has historically been controversial. Recent publications, though varying slightly in the details, share similarities in their approach to classifying HE. Approaches to classifying hand eczema into certain subtypes according to underlying pathogenesis are more common and often discriminate between irritant or allergic contact dermatitis, atopic hand eczema and protein contact dermatitis. The clinical picture is used as an additional feature when etiological factors remain unclear. Recently, the question of whether hyperkeratotic hand eczema might have to be considered as an entirely different and separate disease entity from “hand eczema” in general has been postulated. Additional research has addressed the diagnostic challenges associated with hyperkeratotic hand eczema. Dyshidrotic endogenous eczema has been described as a separate entity in a similar way and poses challenges with regards to diagnosis and treatment. It has been observed in association with allergic contact dermatitis.